Virtual Reality in Military Training to Maintain Indonesian Military Readiness in The Era of Covid-19 Pandemic - K L Herdayatamma (IJHCM (International Journal of Human Capital Management), 2022)
During the COVID-19 pandemic, there have been many changes to human activities, not to mention Indonesia’s military armed forces (TNI). Despite the COVID-19 pandemic, threats to national security still exist. There are even some potential threats that developed during the COVID-19 pandemic and could explode at any time. This article is written based on a qualitative method and used a literature study approach of various literature that related to the topic. The author wants to show the importance of maintaining Indonesian Military Armed Force (TNI) readiness by continuing military education and training with some adjustments. Virtual Reality has become the solution to this problem. With fully immersive system technology, VR can provide an experience that is closest to reality. So that even in a pandemic condition with a policy of restricting human activities, military readiness can still be maintained.